Determinants of Adherence with Malaria Chemoprophylactic Drugs Used in a Traveler’s Health Clinic - Ibrahim Shady (Journal of Tropical Medicine)
Background. The WHO recommends mefloquine, atovaquone/proguanil, and doxycycline for malaria chemoprophylaxis. Adherence to a drug is determined by many factors. Objective. To detect the determinants of travelers’ adherence to malaria chemoprophylaxis. Methods. A prospective comparative study was conducted from January 2012 to July 2013 that included travelers (928 travelers) to malaria endemic countries who visited the THC. They were classified into 3 groups: the 1st is the mefloquine group (396 travelers), the 2nd is the doxycycline group (370 travelers), and finally those who did not receive any drugs (162 travelers). The participants from the 1st and 2nd groups enrolled in the study. Results. Univariate and multivariate analyses were performed. The predictors for adherence in the mefloquine group were travel to an African destination [OR = 51 (6.8–2385)], higher than a secondary school education [OR = 21 (4.1–144.2)], organized travel [OR = 4 (2.1–6.5)], traveling for leisure [OR = 2.1 (1.1–0.4)], and nationality [OR = 2 (1.11–4.00)]. In the doxycycline group, the predictors included higher than a secondary education [OR = 20.1 (4.5–125.1)], organized travel [OR = 11.4 (5.5–20.9)], travel for leisure [OR = 7 (2.3–22.9)], travel to an African destination [OR = 6.1 (0.41–417)], and nationality [OR = 4.5 (2.3–9.5)]. Conclusion. Adherence with malaria chemoprophylaxis could be affected by many factors such as nationality, education, and organized travel.